Steinernema apuliae sp. n. (Rhabditida: Steinernematidae): a new entomopathogenic nematode from southern Italy - Triggiani, Oreste; Mrácek, Zdenek; Reid, Alex (Zootaxa, 2004)
Steinernema apuliae sp. n. has been found in soil samples collected along a saltpan border habitat in southern Italy characterized by a salted silt soil. This species belongs to the long-IJ nematode group represented by Steinernema glaseri (Steiner, 1929) and Steinernema arenarium (Artyukhovsky, 1967) among others. However, it differs from these taxa in some morphometric values such as V%, H%. Females possess asymmetrical, oblique slit vulva, slant vagina and small flap in the vulval opening. These characteristics are more distinct in second generation females which is different from most other steinernematids; the vulva position is behind the mid-body about 57% to 61% of the body length. First-generation females have a conical-like tip bearing 2 to 3 papilla-like protuberances. Male mucron is absent in both generations. Lightly brown spicules have bluntly pointed tip and elongated manubrium. Third-stage infective juveniles are on average over 1000 m long; the position of the excretory pore is posterior (D% 66) and the hyaline layer is less than half the tail length (H% 41 42). Lateral fields are formed by 8 equally distributed ridges. S. apuliae differs from S. glaseri and S. arenarium and is separated by PCR-RFLP analysis of the ITS region. There were no positive cross-breedings among these species.